Dynamic Inguinal Ultrasound (DIUS) in diagnosing groin hernias: Technique, examples and results - Henning Niebuhr; Zaid Malaibari; Halil Dag; Wolfgang Reinpold; Ferdinand Köckerling (International Journal of Abdominal Wall and Hernia Surgery, 2021)
Groin hernia is one of the most common surgical conditions worldwide. Clinical examination can reveal the majority of inguinal hernias. Small inguinal and femoral hernias (in women) may be missed. Dynamic inguinal ultrasound (DIUS) can fill this diagnostic gap. A standardized technique of DIUS is, therefore, important and will be described. The results show high specificity (0.9980) and sensitivity (0.9758), demonstrating the value of the method (which is known to be highly examiner dependent).